Pelatihan public speaking bagi siswa SMA Negeri 5 Barru - Usman, Usman; Hajrah, Hajrah (Universitas Negeri Makassar, 2019)
The Community Partnership Program (PKM) partner is OSIS SMA 5 Barru. The problem is: (1) low motivation in speaking activities, especially in public. The lack of confidence is always experienced by students, so there is no courage to speak in public and (2) limited knowledge, techniques, experience, and public speaking skills. The method used is three stages, namely (1) providing material, (2) practice or simulation, and (3) mentoring. The results achieved are (1) partners have motivation, enthusiasm, and self-confidence can speak in public and (2) partners have knowledge, techniques, experience, and skills when speaking in public, including in supporting activities in carrying out activities in school and community.